Size at Bud Initiation for Wild-Type and Petite Yeast Cells - Bugeja, V. C. (1982)
Cell size at bud initiation shows the same relationship to growth rate in wild-type and petite yeast cells. The nutrient-modulated size control is related to growth rate rather than a change from fermentative to oxidative metabolism.